Formal Thought Disorders–Historical Roots - Jerónimo, Joana; Queirós, Tiago; Cheniaux, Elie; Telles-Correia, Diogo (Frontiers in Psychiatry, 2018)
In this article the authors intend to review in an intelligible and comprehensive way the historical roots of Formal Thought Disorders. Early descriptions of thought disorders date back to the XIX century with Esquirol, but it was in the first half of the XX century that several authors introduced the main features of the actual concept of Formal Thought Disorders. Emil Kraepelin described akataphasia (inability to find the appropriate expression for a thought) in patients with dementia praecox (a term that some years later was replaced by schizophrenia). Bleuler and Kretschmer also identified in schizophrenic patients a generalized “loosening of associations” and Carl Schneider described several Formal Thought Disorders such as derailment, fusion, omission, suspension and drivelling. At the end of the XX century Nancy Andreasen studied the classical descriptions regarding Formal Thought Disorders, reclassified them and also introduced a scale to assess them. Although the specificity of these symptoms in schizophrenia and psychosis has been a source of controversy among the different authors, the importance given to their presence in these mental disorders is universal. We defend that it is crucial that these historical and conceptual elements are grasped in order to assess Formal Thought Disorders for clinical and research purposes.